Questions de méthode en psychiatrie anthropologique - Bernabé, Jean (Anthropologica, 2022)
In a first part, this article discusses the problem of the means of knowledge which are involved in the anthropological quest for "the different other". A distinction is made between the subject's "discourse" and his behavior. At a more abstract level, there appears to be a non-symbolised semantic order which presents itself as a set of formal rules characteristic of "discourse" and of behavior. These rules are verbalised in terms of a frame of reference. This latter is a temporal one. The analysis of a psychiatric case comprizes the secondpart and leads the reader to clear pictures of cultural "discourse" and behavior. The operations of which are non-cultural in comparison with their social context. Those operations are first "temporal", but evoke for "spatial" and "interactional" analogies as well. They connect in a conceptual manner phenomena which are difficult to combine in the logic of a natural language, e.g. affectional conflicts, geographical, political and social reforms, alcoolism and gluttony. This understanding at a more abstract level retraces, however, fundamental cultural experiences.